Science, technology and sustainability. (1st January 2000) - Raven, Peter
As we enter a new millennium, three major areas of public policy concern stand out. The first is the rapid rate at which scientific and technological advancement has transformed human life and the growing concern over environment and sustainability. These processes are already a key feature of international discussions and will continue to dominate international and national public debates for a long time to come. Discussions about the future of biotechnology in the global economy will largely be framed in the context of these three areas of public interest. So far these issues have been discussed in separate forums with little attention to the intricate threads that connect them. This paper seeks to analyse the linkages between science and technology, human welfare and sustainability.